Rice ONAC005-OsMADS50-OsMADS56 interaction downregulates OsLFL1 in promoting long-day-dependent flowering - Jinku Kang; Kiyoon Kang; Sang-Ji Lee; Yejin Shim; Sung-Hwan Cho; Nam-Chon Paek (Crop Journal, 2024)
The transition from the vegetative to reproductive stage (flowering) is a critical stage in the life cycle of plants. Transition to flowering is controlled by a complex photoperiod-dependent network. Here, we report the functional analysis of NAC transcription factor ONAC005 as a positive regulator of flowering in rice. An onac005-1 T-DNA insertion mutant showed late flowering only under long-day (LD) conditions, indicating that ONAC005 is an LD-dependent flowering activator. Expression analysis of flowering time genes revealed that ONAC005 negatively regulates expression of OsLFL1, which is a LD-specific repressor of flowering in rice. Consequently, ONAC005 up-regulates expression of downstream genes Ehd1, Hd3a, and RFT1 under LD conditions. ONAC005 physically interacts with previously reported upstream regulators of OsLFL1, OsMADS50 and OsMADS56. Binding assays showed that ONAC005 binds to the promoter regions of OsLFL1. We further found that the ONAC005-OsMADS50-OsMADS56 complex weakly repressed OsLFL1 at the early vegetative stage and then gradually repressed it at the transcriptional level as the plant developed. Taken together, our results suggest that ONAC005 specifically affects flowering under LD-dependent conditions by interacting with an antagonistic protein complex.